Investigating the reliability and validity of data inputs for building life cycle cost (LCC) - Ayob, Mohd Fairullazi; Abdul Rashid, Khairuddin (2011)
Commentators advocate that most practitioners focus only on conversion but very seldom they consider the reliability and credibility of data inputs of Life Cycle Cost (LCC). The research identified two developed LCC conversion softwares in the Malaysian construction industry: LICCOMS and LCCsoft however it was observed there is a need of a standard procedure and methodology to establish in order to trace, procure and manage data inputs of an asset with reference to LCC. This paper reports part of a three-year programme of research to investigate the current state and practice of LCC in the Malaysian construction industry with specific reference to data inputs of LCC. The research focuses on the data requirements of LCC analysis, where the research gives emphasis on the availability, accessibility, updated and reliability of data inputs for building life cycle cost. A comparative assessment was carried out based on the literature review to ascertain the readiness, appropriateness and accurateness of the data to be used in conversion and monitoring the outputs of LCC analysis. The research methodology employed comprises of a comprehensive literature review and a series of Delphi communication process. The study involved a structured group communication process that procured responses through a number of sequential questionnaires from a group of experts, following by synthesizing and analysing opinions and ideas to attain consensus in generating reliable data for the research.